Spanish travel writing on the Philippines in the 16th century - De Ocampo, Anna Melinda L. Testa (2007)
Travel writing on the Philippines by European and American writers abound in our archives. But it remains largely an unstudied genre since these texts have been read mostly for their descriptive content or for filling in the "gaps in history". These texts have been used to create an image of the early pre-Hispanic or pre-colonial Filipino. Since writings by the Filipinos have been destroyed by the Spanish friars and the ravages of time, these texts by Europeans become crucial to "see" the early Filipino. But looking at these European accounts alongside earlier travel writing by the Chinese, we see that the purposes of travel impinge on the writing of the text. The Spanish accounts, from the Magellan expedition to Legazpi, as well as the seminal texts in the Philippine history such as those by Fr. Chirino, Fr. Plasencia and excerpts from Fr. Colin, show different tropes in travel writing, not just in terms of the cultural background but on the intentions of the traveler himself. The Chinese texts show an interest in trading practices, political order and customs of the natives. I propose the use of five tropes to analyze the Spanish texts. These are: the Marvelous, Appropriation of Space and Naming, the idea of God in history and resistance by the early natives against Spanish colonial rule. This study is limited to the early 16th century travel accounts, since in the later period, writers are influenced by the Enlightenment and necessarily, the tropes will be different.
Thesis (M.A. Comparative Literature)--University of the Philippines, Diliman.
Keywords: Travelers' writings, Spanish -- Philippines -- 16th century